Passive Lossless Snubber for PFC AC-DC Converters - Bodur, Haci; Yesilyurt, Huseyin; Akboy, Erdem (ISTANBUL UNIV-CERRAHAPASA, 2020)
In this study, an improved passive lossless snubber cell for the non isolated pulse width modulation direct current (DC)-DC converter family is proposed. The proposed snubber cell provides soft switching for all semiconductor power devices in the converter under wide input voltage-current and output load ranges. Detailed theoretical analysis is carried out and verified with the implementation of a continuous current mode power factor correction t oost converter having 220-V_AC input, 400-V_DC output, 50-kHz switching frequency, and 1-kW output power. The overall efficiency of the proposed converter at full load increased from 85% in hard switching conditions to 97.5%, thanks to the proposed lossless passive snubber cell. The application of the proposed snubber cell to other DC-DC converters is also presented.
Keywords: Soft switching; passive snubber cell; pulse-width modulation; DC-DC converter; PWM; CELL; VOLTAGE; FAMILY; Engineering